Chile’s Education System: Crafting Policy for the Modern Era. - Corey, Benjamin. (Tufts Archival Research Center, 2018)
This study outlines potential avenues for policy reforms in Chile’s higher education system under the Piñera Administration. Data is drawn from international organizations like the World Bank and the Organization for Economic Co-operation and Development to compare Chile’s quality assurance model and financial assistance resources to those found throughout the developed world. While the country’s academic system has a history of being prohibitively expensive and unable to provide students with the skills necessary to smoothly enter into the job market, recent policy changes have shown that the government is on track to successfully address these problems. Therefore, I will show that the objective for future policy implementations should be to continue this positive trajectory during the Piñera Administration. I plan to demonstrate that the key to achieving this goal is by putting forth policy that can appeal to President Piñera’s conservative ideology while still promoting greater government influence in the academic field.